FIVE SPECIES OF MATUTA (CALAPPIDAE, BRACHYURA, DECAPODA) FROM INDONESIA - Romimohtarto, Kasijan (Marine Research in Indonesia, 1972)
Five species of Matuta from Indonesia i.e. lunaris, planipes, banksii, inermis and cuntispina are differentiated and grouped according to several important morphological characters. Each species is briefly described but extensively illustrated including the first and the second male pleopods. The first male pleopod of M. curtispina is quite different from the other four. The use of the structure of the stridulating organs as one of the important characters in classifying the species is emphasized and a new key is established.